Pembinaan Akhlak Siswa di Lembaga Pendidikan Islam: Implementasi Nilai Keagamaan - Firdaus, Firdaus; Syarif, Miftah; Antony Putra, Ary (Jurnal Pendidikan Agama Islam Al-Thariqah, 2025)
This research was conducted to understand how the implementation of religious values can foster students' moral character. It is essential to explore this topic as many schools are still searching for models or methods to effectively implement these religious values. This study adopts a qualitative research approach, specifically a case study method. The data for this research was collected through interviews. The data was analysed through stages of data reduction, data presentation, and drawing conclusions from the obtained data. In this study, the researcher identified several stages undertaken by schools to implement religious values among students: (1) the stage of programme determination carried out by the school authorities, (2) the implementation of religious values through integration within the learning process, (3) the establishment of a special body as a control mechanism for the programme's implementation of religious values, and (4) a comprehensive evaluation of the programme's execution and the outcomes achieved from the implemented programme